SOCIO-ECONOMIC ANALYSIS OF CONDITIONS OF DEVELOPMENT OF HIGHER EDUCATION INSTITUTIONS - Saidov, Shohruh Mirzo (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article delves into the socio-economic analysis of higher education institutions, investigating the intricate relationship between economic conditions and educational development. Through a mixed-methods approach, quantitative data analysis and qualitative insights illuminate key factors influencing institutional growth, including funding sources, enrollment demographics, faculty-student ratios, and financial sustainability measures. By integrating findings from theoretical frameworks and localized case studies, the discussion underscores the broader societal implications of educational dynamics. The synthesis of insights underscores the imperative for policymakers, administrators, and stakeholders to prioritize equity, innovation, and resilience in shaping the future of higher education.